Experiences of fatigue in daily life of people with acquired brain injury: a qualitative study. Issue 20 (25th September 2021) - Ezekiel, Leisle; Field, Leanne; Collett, Johnny; Dawes, Helen; Boulton, Mary
Abstract: Purpose: To develop an in-depth understanding of how survivors of acquired brain injury (ABI) experience fatigue and how fatigue affects everyday life. Materials and methods: We conducted semi-structured in-depth interviews with 16 adults with ABI fatigue, recruited from support groups in south east UK. Interviews were analysed using the frameworks method. Results: We developed four themes: experiencing fatigue in the context of everyday activities, struggling to make sense of fatigue, coping with fatigue, and adjusting social participation in the context of fatigue. Fatigue was comprised of mental, physical, generalised, and motivational fatigue. Balancing fatigue against participation in daily activities was influenced by coping strategies and social support. Opportunities to socialize or participate in meaningful activities provided incentives for participants to push through their fatigue. Conclusions: This study highlights complex interactions that potentially mitigate the impact of fatigue on everyday life. Educational and self-management approaches to fatigue need to account for different types of fatigue in the contexts of an individual's daily activity. Assessment of fatigue should capture in-the-moment experiences of different types of fatigue and activity. Social support and participation in meaningful activities may help individuals to break the negative cycle of fatigue and inactivity. Implications for rehabilitation: Assessment of fatigue after brain injury should capture the multidimensional nature of fatigue as well as contextual information about exacerbating activities and environments. Development of personalised coping strategies that account for perceived triggers of different subtypes of fatigue may help ABI survivors to broaden their activity and social participation. Social support and opportunities to participate in personally meaningful activities may help prevent or break a negative cycle of fatigue and inactivity for some ABI survivors.